Математичне моделювання евклідових комбінаторних конфігурацій - Пічугіна, О. С. (ХНУРЕ, 2019)
Дисертаційна робота присвячена питанню формалізації задач комбінаторного характеру як задач на скінченних точкових конфігураціях. У ній представлено новий погляд на комбінаторні конфігурації та на його основі запропоновано інноваційні підходи до моделювання цих конфігурацій та застосування в області оптимізації. У роботі вирішено важливу наукову проблему вироблення загальної методології дослідження екстремальних задач на множинах комбінаторних конфігурацій, що полягає у відображенні допустимої множини комбінаторних конфігурацій у евклідів простір, формуванні евклідової постановки екстремальної задачі, застосуванні запропонованої типології до визначення типу отриманої задачі евклідової комбінаторної оптимізації як екстремальної задачі на множині е-конфігурацій та, залежно від класу отриманої задачі, подальшого її розв'язання відповідними методами, що комплексно використовують досліджені алгебро-топологічні та тополого-метричні властивості множин е-конфігурацій, запропоновану теорію їх неперервних функціональних представлень, теорію опуклих продовжень та оцінок мінімумів функцій, а також наявний на даний момент апарат математичного програмування. The thesis is dedicated to formalization of extreme problems of a combinatorial na-ture as optimization problems on finite point configurations in Euclidean space. It presents a new perspective on combinatorial configurations as mathematical objects underlying in-novative approaches to modeling the configurations and their applications in optimization. The steady increase in complexity of the modern real-world problems, that need solving today, puts forward the new requirements for their mathematical modeling and ad-aptation for the application of existing mathematical tools. This necessitates the introduc-tion of new mathematical objects, allowing formalization of these problems, given their discrete-continuous and extreme nature. Such objects, on one hand, should reflect the combinatorial structures that can be singled out in these problems, and on the other hand, should establish a connection between the combinatorial spaces arising in this case and the continuous spaces, such as Euclidean, in order to make the whole arsenal of contemporary theoretical optimization tools applicable to solving the extreme combinatorial problems.The result of the research conducted in this thesis is the solution to an important sci-entific problem of developing a general methodology for studying extreme problems on a combinatorial configuration set. The methodology consists of the mapping of an admissi-ble combinatorial configuration set into Euclidean space, defining the Euclidean formula-tion of the extreme problem, applying the developed typology to determine the type of the obtained Euclidean combinatorial optimization problem as an extreme problem on an e-configurations set. The final step is, depending on the problem type, its solution by rele-vant methods, comprehensively using derived algebraic topological and metric topological properties of e-configuration sets, the theory of continuous functional representation, of convex extensions and minima estimation, as well as classical and modern optimization.
Keywords: комбінаторна конфігурація; евклідова комбінаторна конфігурація; перестановка; розміщення; екстремальна комбінаторна задача; евклідова комбінаторна множина; евклідова комбінаторна оптимізація; опукле продовження; неперервне функціональне представлення; комбінаторний багатогранник; поліедрально-поверхнева множина; декомпозиція; релаксація; combinatorial configuration; Euclidean combinatorial configuration; permutation; partial permutation; extreme combinatorial problem; Euclidean combinatorial set; Euclidean combinatorial optimization; convex extension; continuous functional repre-sentation; combinatorial polytope; polyhedral-surfaced set; decomposition; relaxation